FENOMENA FLUKTUASI HARGA MINYAK NILAM (Cablin benth) BERBASIS AGRIBISNIS: PERSPEKTIF PETANI DI DESA PAMOMBONG, SULAWESI BARAT - Asriani, Asriani; Syahidah, Syahidah; Agustiawan, Agustiawan; Pakpahan, Sartika (Jurnal Riset Multidisiplin Agrisosco, 2025)
This study aims to understand the phenomenon of agribusiness-based patchouli oil price fluctuations from the perspective of farmers in Pamombong Village, West Sulawesi. The research method used is qualitative with in-depth interviews, observation, and documentation techniques. A qualitative approach with a case study design was used to explore farmers' experiences in dealing with uncertain price dynamics, which were then analyzed using SWOT. The results show that patchouli oil price fluctuations are influenced by internal factors such as domestic market structure and the role of farmer institutions as well as external factors such as global market conditions, the impact of which is seen in income, production strategies, and marketing patterns. This study emphasizes the importance of strengthening agribusiness institutions, access to price information, and government policy support in creating a more sustainable and efficient patchouli oil trading system